EROTYPE IDENTIFICATION OF VIBRIO CHOLERAE BACTERIAWHICH ISOLATED FROM ICE AMONGTUBE AND CUBE ICE TYPE IN FOOD AND BEVERAGES SELLER AT DENPASAR CITY, BALI - IGP Dhinarananta; IGM Wijaya P; P Ananta WS; P Yuniadi A; M Agus Hendrayana (Universitas Udayana, 2014)
Cholera is a type of watery diarrhea with specific sign stool containing mucus which resembles rice water. Cholera caused by gram negative bacteria Vibrio cholerae (V.Cholerae). The transmissions of bacteria were through a contaminated food or water.Bali is an international tourism destination with tropical weather where ice is widelyused in food and beverage which bring a risk of cholera through a contaminated ice.Iceshave a risk of bacterial contamination whether from the making and the usage process.Type of ice that widely used were cube and tube ice which each of them have a differentin making and usage process. The purpose of this study is to obtain the contamination ofV.cholera in cube and tube ice. The method of this study is descriptive observationalstudy with quota sampling technique. Sample were obtained from a restaurants andstreet vendor which use a block and tube ice with total 10 sample and 5 for each type ofice.Sample then cultured in Alkaline Peptone Water(APW) and Thiosulfate Citrate Bilesalt Sucrose(TCBS) agar. Bacteriacolony then identified using a gram staining andLatex Serotyping. The result are 3 over 5 (60%) sample of cube ice contaminated byV.cholera O1 Inaba serotype and 3 over 5 (60%) sample of tube ice contaminated byV.cholera O1 Inaba serotype.